Screening and Validation of Rhizobial Strains for Improved Lentil Growth - Tianda Chang; Tao Yang; Meng Ren; Xinghui Li; Xuerui Fang; Bingjie Niu; Hongbin Yang; Lixiang Wang; Ximing Chen (Microorganisms)
Lentil is a nutritionally valuable legume crop, rich in protein, carbohydrates, amino acids, and vitamins, and is also used as green manure. Symbiotic nitrogen fixation (SNF) plays a crucial role in lentil growth and development, yet there is limited research on isolating and identifying lentil rhizobia related to nodulation and nitrogen fixation. This study employed tissue block isolation, line purification, and molecular biology to isolate, purify, and identify rhizobial strains from lentils, analyzing their physiological characteristics, including bromothymol blue (BTB) acid and alkali production capacity, antibiotic resistance, salt tolerance, acid and alkali tolerance, growth temperature range, and drought tolerance simulated by PEG6000. Additionally, the nodulation capacity of these rhizobia was assessed through inoculation experiments using the identified candidate strains. The results showed that all isolated rhizobial strains were resistant to Congo red, and nifH gene amplification confirmed their potential as nitrogen fixers. Most strains were positive for H2O2 and BTB acid and base production, with a preference for alkaline environments. In terms of salt tolerance, the strains grew normally at 0.5–2% NaCl, and six strains were identified as salt stress resistant at 4% NaCl. The temperature range for growth was between 4 °C and 49 °C. Antibiotic assays revealed resistance to ampicillin and low concentrations of streptomycin, while kanamycin significantly inhibited growth. Two drought-tolerant strains, TG25 and TG55, were identified using PEG6000-simulated drought conditions. Inoculation with candidate rhizobial strains significantly increased lentil biomass, highlighting their potential for enhancing crop productivity.